Agregado reciclado: um novo material da construção civil - Souza, Leandro Moreno de; Assis, Cleber Decarli de; Souto, Silvia Barroso Gomes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The civil construction sector consumes during its process a large amount of material, which somehow ends up generating great scales Waste Construction and Demolition better known as RCD ‘s waste in certain major centers reach a number of ratios concern and may in various waste deposits its share being 50% of the total which is arranged in a predetermined location . With these data one can understand the need to think about the reuse of this waste ends up being extremely important for both the environmental context in which they alleviate the impacts caused even skin to the environment , as well as economic character . In several studies that examines the feasibility of reuse of construction waste , it is observed that there is no warranty in relation to the parameters that ensure safety when used in concrete artifacts . Therefore, this study aims to determine the strength parameters of concrete blocks and concrete , with the use of ceramic aggregates and concrete aggregate considered whites.